Greek Inscriptions on the East Bank - Nilsson, Maria (Brill, 2023)
For the first time, this book presents the complete collection of Greek inscriptions of Gebel el-Silsila East - Ancient Egypt's largest and most important sandstone quarry, including lists of names and professions of individuals involved in the quarry expeditions. The inscriptions are described, illustrated and analysed and placed within their archaeological context based on careful documentation in situ with up-to-date methodology. The work makes substantial contributions in the form of novel and improved readings and interpretations of known texts and of the new publication of texts discovered through the fieldwork. It is the first volume of three dealing with Graeco-Roman inscriptions on the east bank, with the following two volumes to cover the demotic texts and quarry marks respectively.